2004
DOI: 10.1007/s00406-004-0471-8
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the psychopathology of depressed inpatients

Abstract: In the last few years there has been increased scientific effort to describe the gender-specific psychopathological features of depression. Until now these studies have not been entirely conclusive, which could be the result of methodological difficulties. This report investigates sex differences in the symptom presentation in an inpatient population: 104 female and 113 male patients suffering from a depressive episode according to ICD-10 were admitted to the inpatient treatment at the Department of General Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
3
35
1
6
Order By: Relevance
“…One of the drawbacks of many of the previous studies was that only a narrow scope of typical depressive symptoms was assessed. Recently, two studies have been published evaluating psychopathology with the AMDP system [29, 43]. However, both studies have yielded only subtle gender differences in the symptom pattern, which suggested an exaggeration or distortion of gender-bound role behavior during depression, but failed to entirely confirm the hypothesis of a distinct male depression, which may be due to insensitivity of the AMDP items.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the drawbacks of many of the previous studies was that only a narrow scope of typical depressive symptoms was assessed. Recently, two studies have been published evaluating psychopathology with the AMDP system [29, 43]. However, both studies have yielded only subtle gender differences in the symptom pattern, which suggested an exaggeration or distortion of gender-bound role behavior during depression, but failed to entirely confirm the hypothesis of a distinct male depression, which may be due to insensitivity of the AMDP items.…”
Section: Discussionmentioning
confidence: 99%
“…As established by Fava et al [8], subjects were classified as having anger attacks, if they exhibited the following criteria during their last depression: a 6-month baseline of irritability in combination with a tendency to overreact, at least one anger attack per month and at least 4 additional autonomic arousal symptoms and behavioral outburst. According to our prior study [29], we assumed that there would not be any sex differences in total HAD and BDI scores. The secondary objective of our study was an exploratory analysis of gender differences in regard to the items of the GMDS and the ADDS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequentemente, a análise e discussão dos resultados desse tipo de trabalho os comparam a resultados obtidos por estudos junto a populações diferentes (neste caso, estudos com pacientes de países ocidentais). Contudo, enquanto nesses trabalhos o objetivo principal é a "descrição", sendo a "comparação" permitida um desdobramento, estudos como o de Turkel et al (2004) e o de Winkler et al (2004) são mais especificamente dirigidos a este segundo propósito e já incluem duas populações distintas em suas avaliações. Nestes dois casos, especificamente, a atenção se dirige a possíveis diferenças sintomáticas do transtorno obsessivo compulsivo e quadros depressivos, respectivamente, em populações feminina e masculina.…”
Section: Tipos De Investigação Psicopatológica Em Psiquiatriaunclassified
“…Other symptoms of depression in fathers may include: withdrawal from social interactions, indecisiveness, cynicism and irritability, and also avoidance behavior, alcohol abuse, drug use, extramarital sex and violent behavior towards the partner. Male emotions might occur more as fear or anger than sadness [11]. When no uniform assessment criteria are available, the symptoms of paternal postnatal depression may be misunderstood.…”
Section: Research On Paternal Postnatal Depres-sion -A Reviewmentioning
confidence: 99%